Unite and conquer : how to build coalitions that win-- and last - Sinema, Kyrsten (BK currents book., 2009)
Shares how we can put together broad-based coalitions that advance the progressive agenda rather than simply make us feel good about the purity of our ideals. This book argues that we must let go of our preconceived notions about who our opponents are, how they think, and what specific outcomes we're aiming for.